Transcriptional and replicational activation functions in the bovine papillomavirus type 1 E2 protein are encoded by different structural determinants. - Abroi, A (1996)
A set of E2 proteins with mutations in the amino-terminal transactivation domain was made by a scheme called clustered charged-to-alanine scan. These mutant E2 proteins were tested for expression, stability, and compartmentalization in cells and for sequence-specific DNA binding, as well as in functional assays for transcriptional and replicational activation. We identified four groups of mutants. First, mutants K111A, K112A, and E176A were unable to activate replication and transcription because of oligomerization-induced retention of oligomers in the cytoplasm. Second, although fractions of the mutant proteins E74A and D143A/ R172C existed in the oligomeric form, they were localized in the nucleus. Certain fractions of these proteins existed as a dimer able to form a specific complex and activate replication; however, these proteins were inactive in transcriptional activation. Third, mutants R37A and D122A were localized in the nucleus, existed in the dimeric form, supported replication efficiently, and were severely crippled in transcriptional activation. The fourth group of mutants did not differ considerably from the wild-type protein. The activation of transcription by the wild type as well as mutant E2 proteins was dependent on the concentration of input E2 expression vector DNA and had a bell-like shape. We suggest that the reduction of transcriptional activation at higher E2 concentrations, the self-squelching activity, is caused by oligomerization of the E2 transactivator and is one of the mechanisms for the regulation of E2 activity. Our results also show that transcriptional and replicational activation activities are encoded by different determinants in the E2 protein.